Zakat disclosure of zakat institutions : perceptions of accounting and non-accounting students - Khin Ohnmar Tun (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2019)
Studies about disclosure of Islamic financial institutions is still lacking. There are some zakat disclosure studies in the perception of zakat recipients but there is no specific study related to students as the zakat recipient. The objective of the study is to investigate the perceptions of accounting and non-accounting students on the disclosure of financial and non-financial information by zakat institutions. The second objective is to identify the perceptional difference between the accounting and non-accounting students on information disclosure of zakat institutions. Downward Accountability concept and Resource Dependence Theory were applied as theoretical framework of this research. A total of 2109 questionnaires were sent to the Zakat Department of a public institution of higher learning in Malaysia. The questionnaires were distributed to the students who are studying in different fields of study in different branches of the university in Malaysia and at the same time are zakat recipients as well. The completed 1018 questionnaire were received and only 544 questionnaires were usable. The number of respondents is 127 and 417 for accounting and non-accounting respectively. The study uses descriptive analysis and t-test to analyse the results of the study. The study found out that having prior accounting knowledge can affect the perception of respondents for disclosure items for zakat institutions. The findings show that accounting students perceive that disclosure of financial information is important whereas non-accounting students perceive disclosure of non-financial information is as important as the financial information. The study found that there is a difference for rating the disclosure items of zakat institutions between accounting and non-accounting students, however, only 36% have significant difference and 64% is not different significantly. The current research is limited due to using only questionnaire survey as well as respondents are students who are zakat recipients and comparison done is only between accounting and non-accounting students. There should have the awareness program for non-accounting students to educate them to understand more about the disclosure of zakat institutions, particularly on the importance of financial information to be disclosed.